Pengaruh status gizi anak terhadap perkembangan bahasa ekspresif anak usia 2-3 tahun di Kelurahan Tamanwinangun Kabupaten Kebumen - Nuryuliasih, Salfah; Sumanto, Reni Pawestuti Ambari (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
Early childhood education is the beginning of formal education for children and the role of teachers here is vital in educating the lives of the nation's children. Obviously, expertise, professionalism, and good character are needed by a teacher. This research's background is that the work discipline level for ECE teachers in Tahunan District is still low. Teachers often leave the classroom while the learning process is ongoing, there are many teacher interns in short periods of time, there is still a lack of love for doing this job, and there are not many references regarding the variable of teacher loyalty at the ECE level. A teacher's loyalty can be identified from various factors, both internal and external. Loyalty means respecting and loving everything without coercion. From the existing problems, the researcher aims to identify the influence of teachers’ work discipline on their loyalty towards the ECE institutions in Tahunan District. The research method used is a quantitative survey research method with random sampling techniques. The results of research on 155 ECE teacher respondents in Tahunan District showed that the work discipline of PAUD teachers is very high is 67%. The same with their discipline, their loyalty is also very high is 64%. The analysis results used were with the help of IBM SPSS 25, Chi-Square calculation results with sig value results. (2-tailed) is 0.000. From these calculations, it can be concluded that there is indeed an influence of teacher work discipline on loyalty to ECE institutions in Tahunan District.